Public expenditure’s role in reducing poverty and improving food and nutrition security: Preliminary cross-country insights based on SPEED data - Takeshima, Hiroyuki; Smart, Jenny; Diao, Xinshen (International Food Policy Research Institute, 2021)
Public expenditures (PE), their sizes, and allocations across sectors, are some of the important instruments for the public sector to contribute toward sustainable development goals (SDGs). However, knowledge gaps remain as to how PEs have actually contributed to key SDG outcomes in the past, including the eradication of poverty and hunger, and the improvement in food and nutrition security in sustainable manners (SDGs 1 and 2). This study aims to partly fill this knowledge gap using the Statistics on Public Expenditures for Economic Development (SPEED data) and various country-level panel data. We find that PEs in different sectors have been significantly associated with key indicators under SDGs 1 and 2. Specifically, greater PEs for agriculture and health sectors have had relatively positive effects on total factor productivity growth in agriculture, reduced consumer food price indices, reduced poverty, reduced stunting, underweight or overweight among children under 5. A greater PE for agriculture has also been weakly associated with enhanced biodiversity. These relationships are observed for a broad class of countries, but somewhat stronger for countries that had been classified as low- or lower-middle-income in 2000. Greater PEs for education and social protection, which have been generally higher than PEs for agriculture and health, have had more mixed effects on these outcomes. While continued analyses are required to better understand the complex linkages between PE and these outcomes, the current study offers useful preliminary insights.